2020
DOI: 10.1177/1049909120979179
|View full text |Cite|
|
Sign up to set email alerts
|

Educating Internal Medicine Residents on Palliative Medicine and Hospice Care at a Community Teaching Hospital

Abstract: Background: The Accreditation Council of Graduate Medical Education (ACGME) currently requires Internal Medicine (IM) GME programs to incorporate educational opportunities for training and structured experiences in Palliative and Hospice Medicine. Miscomprehension of the differences between palliative medicine and hospice care is a barrier for IM residents ordering palliative consults as many residents may underutilize palliative medicine if a patient is not appropriate for hospice. Objective: This educational… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 10 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…Further, several universities present these topics through workshops and didactics entitled "end-of-life care" and "death and dying. " Studies have shown that medical trainees do not understand the difference between PC and providing hospice or EOL care to terminal patients [16]. PC can be provided in conjunction with life-prolonging or curative modalities, and has been shown to improve the quality of life of patients with serious illness, regardless of whether or not that illness is terminal.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, several universities present these topics through workshops and didactics entitled "end-of-life care" and "death and dying. " Studies have shown that medical trainees do not understand the difference between PC and providing hospice or EOL care to terminal patients [16]. PC can be provided in conjunction with life-prolonging or curative modalities, and has been shown to improve the quality of life of patients with serious illness, regardless of whether or not that illness is terminal.…”
Section: Discussionmentioning
confidence: 99%
“…PC can be provided in conjunction with life-prolonging or curative modalities, and has been shown to improve the quality of life of patients with serious illness, regardless of whether or not that illness is terminal. As such, this confusion can become an impediment to the provision of PC services to non-terminal patients [16]. This also likely contributes to limited student awareness of PC as a distinct medical specialty.…”
Section: Discussionmentioning
confidence: 99%
“…Medical residents may struggle to distinguish palliative from hospice care, 24 and we believe that a meaningful HPM clinical experience should highlight the key components of hospice. The term “hospice care” both refers to a philosophical approach to care and often carries connotations regarding where care will be delivered.…”
Section: Core Elements Of a Clinical Experience In Hpmmentioning
confidence: 99%